倫理審查的制度歷史、運行現狀與困境: The History, Status, and Dilemmas of Ethics Reviews - DENG, Rui (International Journal of Chinese & Comparative Philosophy of Medicine, 2010)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 西方文化和原則主義的生物醫學倫理審查制度大有“普惠全球”之勢，但是從國際文獻的制訂歷史追溯倫理審查要求的修改變化，會發現倫理審查要求的弱化和無窮倒退的現象。本文將結合當前西方倫理審查的運行現狀，對倫理審查制度面臨的理論和實踐困境進行分析。 Since the 1970s, the ethics review system has become an important measure to protect human life. International organizations have ceaselessly revised and perfected the rules of several international ethics documents, carried out ability training for ethics reviews on a global scale, helped many countries to set up ethics committees, and attempted to promote the Western ethical culture and principle of “universal ethics.” However, if we investigate the history of the changes in the requirements of ethics reviews coded in the relevant international documents and enactments, we find that the requirements of ethics reviews for medical research have become weakened and have substantially regressed. The Western approach to the ethics review has no means of ensuring that investigators obey the ethics review system. It is also unable to secure common ground and set aside differences when confronted with a pluralist culture. This weakens its ability to review and supervise. The current state of the Western ethics review also displays some negative features, such as a loosely organized structure, commercialization stimulated by conflicts of interest, disagreement over conclusions (especially for research projects involving multiple research centers) due to pluralist cultures and systems of morality, the limited protection of human subjects due to poor review and supervision, and the imposition on researchers of very complex review processes. The system of ethics review is also beset by several dilemmas. The first is the suspicion of ethics imperialism. International documents attempt to provide a universal frame and impose the values of certain moral communities on others. Second, the ethics principles proposed by Beauchamp and Childress seem to be the foundation of many international documents, yet reflect only a small part of American morality, and cannot always be applied to other cultures and customs. They have been attacked by virtue theory, casuistry, feminism, and communitarianism alike. Third, the history of the revision of international ethics documents suggests that ethics reviews often fall into a vicious circle: scientific research must be reviewed by an ethics committee, and the ethics committee must be reviewed by an external institute, but who reviews the external institute? This essay contends that the Western ethics review system is based on Western human rights theory and the religious view of original sin, in that the review process must be enforced to prevent the evil in human nature. This epistemological foundation has caused many problems and dilemmas, as stated. To resolve these problems and dilemmas, we need to re-examine the foundations of ethics reviews. This essay argues that due to the reality of cultural and ethical pluralism, it is difficult, if not impossible, to seek a global or universal ethical theory that will guide all ethics review practices. Finally, this essay puts forward a proposal for reconstructing Chinese ethics reviews by drawing on intellectual and ethical thought in Confucian resources. Confucianism emphasizes the cultivation of virtue and self-improvement, which means that the good of the individual primarily derives from self-discipline. In a scientific research field, this suggests that investigators should do good voluntarily and conscientiously. This idea should be applied in the construction of a harmonious relationship between ethics committees and researchers. DOWNLOAD HISTORY | This article has been downloaded 114 times in Digital Commons before migrating into this platform.